Perlindungan Hukum bagi Nasabah Bank Selaku Konsumen di Bidang Perbankan - Rum, Gresia Wulaning; Aryana, Rizka Afi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The role of banking as a financial intermediary institution is very important in economic development, but the bargaining position of customers is often weaker compared to the bank. Therefore, clear regulations are needed to protect the rights of customers. This article examines the role of the Consumer Protection Law (CPL) and other relevant regulations, including the role of the Deposit Insurance Corporation (DIC) and provisions in the Bank Indonesia Regulation (BIR) regarding customer complaint resolution and banking mediation. The study results indicate that legal protection for customers needs to be enhanced through the implementation of stricter regulations and more effective mediation processes to minimize the power imbalance between banks and customers.